2022
DOI: 10.3389/fcvm.2021.777327
|View full text |Cite
|
Sign up to set email alerts
|

Potential Clinical Value of Biomarker-Guided Emergency Triage for Thoracic Aortic Dissection

Abstract: Aim: Thoracic aortic dissection (TAD) is a high-risk vascular disease. The mortality rate of untreated TADs in 24 h was as high as 50%. Thus, rapid diagnosis of TAD in the emergency department would get patients to the right treatments to save their lives.Methods: We profiled the proteome of aortic tissues from TAD patients using a label-free quantification proteomics method. The differentially expressed proteins were screened and subjected to bioinformatics analysis. Candidate biomarkers were selected and val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 65 publications
1
0
0
Order By: Relevance
“…Differential protein studies of thoracic aortic dissection and normal aortic tissue showed high expression of MIF. 22 Similar results were seen in abdominal aortic aneurysm specimens, the expression of MIF and MMPs was enhanced in ruptured abdominal aortic aneurysm specimens compared to stable abdominal aortic aneurysm and normal aortic specimens. 23 These results suggest the possibility of MIF as a biomarker for the identification of AD and assessment of prognosis.…”
Section: Introductionsupporting
confidence: 74%
“…Differential protein studies of thoracic aortic dissection and normal aortic tissue showed high expression of MIF. 22 Similar results were seen in abdominal aortic aneurysm specimens, the expression of MIF and MMPs was enhanced in ruptured abdominal aortic aneurysm specimens compared to stable abdominal aortic aneurysm and normal aortic specimens. 23 These results suggest the possibility of MIF as a biomarker for the identification of AD and assessment of prognosis.…”
Section: Introductionsupporting
confidence: 74%